Incontinentia pigmenti in the neonatal period - Rodrigues, V (2011)
Incontinentia pigmenti (IP) is a rare multisystem disease, X linked dominant disorder. As all X linked dominant diseases, it is usually male-lethal. Female newborn admitted to the neonatal intensive care unit on the first day of life was diagnosed as having probable herpetic infection with vesicular skin lesions distributed on upper right limb and inferior limbs. Family history showed that her 22-year-old mother had hypopigmented lesions on the lower limbs and her 13-month-old sister had hyperpigmented lesions on the trunk and limbs. In newborns, herpes infection emerges as the principal diagnosis of vesicular rash, due to the importance of precocious diagnosis and treatment. Other hypothesis must be considered in a newborn with vesicobullous rash, such as IP.